TRAINING AND COMMUNITY MENTORING ON THE PRODUCTION OF VIRGIN COCONUT OIL (VCO) AND NATA DE COCO IN PADALEU SUBDISTRICT, KENDARI CITY: PELATIHAN DAN PENDAMPINGAN MASYARAKAT DALAM PEMBUATAN VIRGIN COCONUT OIL (VCO) DAN NATA DE COCO DI KELURAHAN PADALEU KOTA KENDARI - Baihaqi; Sakir; Fatahu; Windayani; Ika Rezvani Aprita; Sri Agustina (PT. ROCE WISDOM ACEH, 2026)
Padaleu Subdistrict, Kendari City, has significant potential for coconut resources, yet its utilization remains limited to low-value-added products. This community service activity aims to enhance the local community’s knowledge and skills through training and mentoring in producing Virgin Coconut Oil (VCO) and nata de coco as value-added coconut products with economic potential. The implementation method includes preparation, training through lectures and hands-on practice, production mentoring, and evaluation using pretest-posttest, skill assessments, and production outcomes. The results show an increase in participants’ knowledge, with an average pretest score of 52.44 rising to 72.88 in the posttest. Participants’ skills also improved, with the average score increasing from 2.15 to 3.31 on a 1–4 scale. The production success rate for VCO was 84%, while for nata de coco it was 56%, with a contamination rate of 20%. The difference in success rates indicates that VCO technology is easier to adopt than nata de coco, which requires stricter sanitation controls and fermentation processes. The activity is considered effective in enhancing the community’s capacity for coconut processing, given its local potential. Further mentoring is needed to improve product quality consistency, especially nata de coco, to ensure its sustainability and competitiveness as a household-based business.